A sustainable approach to produce yeast lipid by utilizing marine macroalgae biomass. (15th April 2023) - Nanda, Manisha; Jaiswal, Krishna Kumar; Negi, Jyoti; de Farias Neves, Fábio; Ranjitha, J.; Vlaskin, Makhail S.; Grigorenko, Anatoly V.; Chauhan, P.K.; Kumar, Vinod
Graphical abstract: Highlights: Yeast lipid was produced by utilizing marine macroalgae biomass. Microwave-mediated hydrolysis technology was used to release glucan from macroalgae. Yeast was genetically modified by ethyl methanesulfonate (EMS) into mutants. Hydrolysis waste residues were converted into activated carbon. Integrated approach for production of yeast lipid, activated carbon and animal feed. Abstract: Marine macroalgae have qualities to utilize it as feedstocks to produce wide spectrum of biofuels, chemicals, and bioactive compounds. Microorganisms play an important role in converting macroalgae biomass into high value products, and genetic modification have been developed to increase their capabilities. The present work has investigated the escalation of lipids by ethyl methanesulfonate (EMS) mutagenesis in oleaginous yeasts and their simultaneous waste-free cultivation in underutilized hydrolyzed macroalgae biomass. After microwave-mediated hydrolysis of the macroalgal biomass, 37 g of glucan per 100 g of biomass were recovered. The examined mutants were further cultivated in microwave-mediated hydrolyzed macroalgae biomass. This study has focused on assessing lipid induction in yeast of EMS mutants. The yeast mutants have shown enhanced maximum biomass (2.1 g/L) with lipid content (47 %).